Length of stay in long-term care facilities: a comparison of residents in six European countries. Results of the PACE cross-sectional study - Katherine Froggatt; H Roeline Pasman; Thomas Keegan; Sheila Payne; Lieve Van den Block; Lara Pivodic; Danni Collingridge Moore; Rauha Heikkila; Viola Kijowska (BMJ Open)
Objectives This paper aims to investigate resident, facility and country characteristics associated with length of stay in long-term care facilities (LTCFs) across six European countries.Setting Data from a cross-sectional study of deceased residents, conducted in LTCFs in Belgium, England, Finland, Italy, the Netherlands and Poland.Participants All residents aged 65 years and older at admission who died in a 3-month period residing in a proportional random sample of LTCFs were included.Primary and secondary outcome measures The primary outcome was length of stay in days, calculated from date of admission and date of death. Resident, facility and country characteristics were included in a proportional hazards model.Results The proportion of deaths within 1 year of admission was 42% (range 32%–63%). Older age at admission (HR 1.04, 95% CI 1.03 to 1.06), being married/in a civil partnership at time of death (HR 1.47, 95% CI 1.13 to 1.89), having cancer at time of death (HR 1.60, 95% CI 1.22 to 2.10) and admission from a hospital (HR 1.84, 95% CI 1.43 to 2.37) or another LTCF (HR 1.81, 95% CI 1.37 to 2.40) were associated with shorter lengths of stay across all countries. Being female (HR 0.72, 95% CI 0.57 to 0.90) was associated with longer lengths of stay.Conclusions Length of stay varied significantly between countries. Factors prior to LTCF admission, in particular the availability of resources that allow an older adult to remain living in the community, appear to influence length of stay. Further research is needed to explore the availability of long-term care in the community prior to admission and its influence on the trajectories of LTCF residents in Europe.